RW - Rachel Whiteread - Mullins, Charlotte 1972- (Tate Publishing, 2017)
"Rachel Whiteread has single-handedly expanded the parameters of contemporary sculpture with her casts of the outer and inner spaces of familiar objects, sometimes in quiet monochrome, sometimes in vivid jewel-like colour. She won the Turner Prize in 1993, the same year as her first large-scale public project, House, a concrete cast of a nineteenth-century terraced house in London's east end. This book by writer and editor, Charlotte Mullins - the first significant survey to examine Whiteread's career to date - has been substantially updated with a new chapter containing ten major works, including Tate's Turbine Hall installation Embankment and Cabin, Whiteread's first permanent public sculpture in America."--BOOK COVER.
Keywords: Whiteread, Rachel -- 1963-; Whiteread, Rachel / 1963- / Criticism and interpretation; Bildband